Entry in liberalized railway markets: The German experience - Rafael Lalive; Armin Schmutzler (University of Zurich, Socioeconomic Institute, 2007)
In Germany, competitive franchising is increasingly being used to procure passenger railway services that were previously provided by a state monopolist. This paper analyzes 77 tenders that differ with respect to network size, service frequency, contract duration and the proximity to other lines that are already run by competitors of DB Regio, a subsidiary of the successor of the former state monopolist. Our analysis shows that competitors are more likely to win small networks and more recent auctions. Other controls such as contract duration and the adjacency to other lines run by entrants are insignificant.
Keywords: D43; D44; R48; 330; competition for the market; liberalization; passenger railways; procurement auctions; Eisenbahnpolitik; Deregulierung; Privatisierung; Ausschreibung; Personenverkehr; Schätzung; Deutschland